2017
DOI: 10.1149/07801.2489ecst
|View full text |Cite
|
Sign up to set email alerts
|

Development and Test of a Solid Oxide Fuel Cell Subsystem with a Low Temperature Anode Off-Gas Recirculation

Abstract: At the Forschungszentrum Jülich, an SOFC subsystem was built and operated. This subsystem consists of the well-established integrated module, combined with a low temperature off-gas recirculation loop. The recirculation loop is driven by a hermetic side-channel blower that operates at gas temperatures of 160°C. During the test phase, a system fuel utilization of 93% and electrical efficiencies of more than 60% could be demonstrated with the subsystem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Figure 9 shows the comparison between the measured isentropic total to total fan efficiencies and power as defined in eqs. (2) to (4). The experiments mean ambient pressure was 0.965 bar ± 0.004 bar, the total fan inlet temperature 200 • C ± 2 • C, and the rotational speed 50 krpm, 70 krpm, ..., 150 krpm, and 168 krpm ± 1 krpm.…”
Section: Evaluation Of the Heat Dissipation By Shaft Lossesmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 9 shows the comparison between the measured isentropic total to total fan efficiencies and power as defined in eqs. (2) to (4). The experiments mean ambient pressure was 0.965 bar ± 0.004 bar, the total fan inlet temperature 200 • C ± 2 • C, and the rotational speed 50 krpm, 70 krpm, ..., 150 krpm, and 168 krpm ± 1 krpm.…”
Section: Evaluation Of the Heat Dissipation By Shaft Lossesmentioning
confidence: 99%
“…Their conclusion is that an electrical net efficiency of up to 64.9 % and a utilization ratio of up to 97.2 % are theoretically possible. Peters et al [4] experimentally demonstrated the technical feasibility of a 2.5 kW e SOFC stack with AOR reaching an electrical net efficiency of 58.5 %. They claim that if a new stack had been used instead of an aged one the efficiency would have been at least 5 points higher.…”
Section: Introductionmentioning
confidence: 99%
“…While market penetration of small scale solid oxide fuel cell systems accelerates , efforts are being devoted to increasing stacking and reaching higher efficiencies in SOFC systems through the implementation of recirculation loops . On the electrolysis side, tremendous progress has recently been achieved in demonstrating commercially viable lifetimes and scaling up SOEC technology .…”
Section: Introductionmentioning
confidence: 99%
“…The basic approach of improving the efficiency of simple once-through SOFC systems is the increase of the global fuel utilization FU while maintaining a suitable local fuel utilization FU at stack level. Two different pathways have been discussed in literature: (i) single-stage SOFC module with anode off-gas recirculation [25][26][27], and (ii) two-stage SOFC module with a fuel regenerator between the modules [13][14][15]28].…”
Section: Sofc Systemsmentioning
confidence: 99%
“…After that, the air stream is heated up by the hot Fig. 1 Flowsheet of the considered SOFC/AGR system according to Peters et al [25].…”
Section: Sofc/agrmentioning
confidence: 99%